Identification of sequence polymorphisms in the D-Loop region of mitochondrial DNA as a risk factor for gastric cancer. (3rd March 2016) - Wang, Huiying; Wang, Yingnan; Zhao, Qun; Guo, Zhanjun; Zhang, Fengbin; Zhao, Yue; Zhang, Ruixing
Abstract: The accumulation of single nucleotide polymorphisms (SNPs) in the displacement loop (D-Loop) of mitochondrial DNA (mtDNA) has been identified for their association with cancer risk in different types of cancers. We investigated the gastric cancer risk profile of D-Loop SNPs in a case-control study. The frequent alleles of nucleotides 73G/A, 235A/G, 309C/C insert, 324C/G, 16, 362T/C and 16, 519C/T were significantly associated with an increased risk for gastric cancer, whereas the frequent alleles of nucleotides 523–524AC/del were associated with resistance to gastric cancer. In conclusion, SNPs in the mtDNA D-Loop were found to be valuable markers for gastric cancer risk evaluation.